(3GdJYQja HGdeUWdM GdTQjas - (3TgGH GdOjf CHj GdYHGS CMeO Hf aVd Gddg GdYeQjs ((3MeRI Hf bGSe Hf GdTgGHi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ejR ebGOjQ GdQJH , hbff GdbhGfjf MJi dGjHbi SHjd def YJH s
(3BNQgG (B:s
(3hGddg jhabfG deG gh GUdM hjaJM YdjfG abO bQYfG HGHi hGddg jaJM GdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3ai SHYI CbSGes
(3fSNI NRGFfjI NRGFfjI fajSIs
(3HQSe GdNRGfI GdZGdjI GdehdhjI GdRjfjI YeQ CHj GdaGM hcjd HjJ GdeGd s
(3cJHJ ai MjGI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs